Thermostabilizer for Polyvinyl Chloride-development of Synergistic Compounds - Lutfullaev, S.Sh.; Tavashov, Sh.X.; Dostmuradova, M.F. (Journal of Mechanical Engineering, 2024)
Thermostabilizer-synergistic mixtures with double salts of T-product for PVX were developed and their synergism efficiency phenomena were studied using DTA and TGA methods. The mixtures of thermostabilizers synergics of mixed salts of the product – T for PVCh were worked out by the methods of DTA and TGA and the effect of synergism was studied. This study aims to develop thermostabilizer-synergistic mixtures with double salts of T-product for polyvinyl chloride (PVC) and to investigate their synergistic efficiency using Differential Thermal Analysis (DTA) and Thermogravimetric Analysis (TGA) methods. The research involved synthesizing stabilizers, preparing PVC mixtures, conducting heat resistance tests, and analyzing the data obtained. The efficiency of the synergistic mixtures was evaluated through DTA and TGA to assess their impact on the thermal stability and degradation behavior of PVC. The study found that the synergistic mixtures significantly enhanced the thermal stability of PVC. The results indicated that the mixtures, particularly those involving lead salts of T-product, demonstrated a pronounced synergistic effect, delaying the onset of thermal degradation and improving overall stability. The effectiveness of the stabilizers was 2-3 times higher when used in mixtures compared to individual use. The optimal ratio for maximum stabilization efficiency was found to be 1:1, with specific mixtures showing an induction period of up to 120 minutes. The developed thermostabilizer-synergistic mixtures with double salts of T-product effectively enhance the thermal stability of PVC. The synergistic interactions between the components contribute to improved performance, making these mixtures promising candidates for enhancing the durability and lifespan of PVC materials. This advancement addresses critical issues related to environmental sustainability, performance enhancement, cost reduction, and market expansion, ensuring that PVC remains a viable and valuable material for a wide range of applications.